Projecto e património edificado em São Paulo. Três casos como práticas de mudança. - Carolina Miguel dos Santos Barreiros (2013)
The city's forms are defined by the set of relationships built between the placeand its inhabitants. These relationships acquire meaning over time as referencesand values, and become part of the collective, social, and urban heritage.The discomfort felt in São Paulo arises from the perception of a context in whichthe construction of the city is far from a shared and coherent system, often detatchedfrom its specific historical and spatial definitions.The motivation for this work came from the desire to study contemporary architecturalpractices on existing buildings, which seem unusual within the currentstatus quo of the city: demolition and new construction.The latest interventions on the headquarters of Correiros e Telégrafos de SãoPaulo (São Paulo's Posts and Telegraphs), Mário de Andrade Library and Casa daImagem reflect a new position on the architectural practice and its relationship withthe city. These three projects diverge from the general line of action, as part of theproduction of some architecture offices whose work has been capable of creatingqualified space.By analyzing these three case studies in a structured way, this work aims tounderstand how, and if, the values identified by the architects on the existing buildingswere integrated in the new proposals. Beyond the drawings, it was intended tounderstand the projects' stages of implementation and the challenges faced by thevarious stakeholders. From this standpoint, it was attempted to consider how thesocio-political context interfered with each process of development.